Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1002/mrm.1910330207
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and Magnetization Transfer in Experimental Myonecrosis in the Rat

Abstract: Experimental myonecrosis--induced by injection of notexin into rat tibialis anterior muscle--and subsequent regeneration were studied from 1 h to 20 days postinjury with magnetic resonance imaging using conventional and magnetization transfer sequences, and these findings were correlated with histopathology. MR images revealed necrosis within 1 h postinjection. Histopathologically, necrotized fibers enlarged and intercellular spaces widened, indicating intracellular and extracellular edema, which began to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Indeed, histopathology of muscle biopsies confirmed swollen muscle fibres with the minimal presence of inflammatory cells. These results are consistent with previous studies in which hyperintensity of T 2 WI has been reported in rhabdomyolysis patients [7,9] and experimental myonecrosis models [23]. In our experiment, ischaemic muscle T 2 values peaked 6 h post ischaemia but reduced in the following hour.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, histopathology of muscle biopsies confirmed swollen muscle fibres with the minimal presence of inflammatory cells. These results are consistent with previous studies in which hyperintensity of T 2 WI has been reported in rhabdomyolysis patients [7,9] and experimental myonecrosis models [23]. In our experiment, ischaemic muscle T 2 values peaked 6 h post ischaemia but reduced in the following hour.…”
Section: Discussionsupporting
confidence: 94%
“…Among dystrophic processes, especially in muscle necrosis, the intramuscular water concentration and extracellular components are increased, with the water imbalance having been induced by the deficiency of sarcolemmal membrane integrity. 19,26,38 CHESS-T2WI may be one of the tools to solve this problem, because the sequence can selectively cancel fat tissue signals.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to eccentric exercise, a delayed increase in the T2 has been observed that peaks 2-6 days after exercise (12,39). This delayed increase correlates to histological assessment of muscle injury in both humans (30) and animals (26) and with changes in other traditional markers of muscle injury such as soreness, serum creatine kinase levels, and isometric force loss (7,12,38).…”
mentioning
confidence: 93%
“…Debate remains as to the mechanism responsible for this prolonged increase in relaxation time that persists long after other markers of injury have returned to baseline levels. The initial delayed response, occurring during the first week, has been shown correlate with histological assessment of muscle injury in both humans (30) and animals (26) and follows a similar time course to traditional markers of muscle injury such as soreness, serum creatine kinase levels, swelling, and force loss (7,12,38). It has been suggested that this initial response tracks transient damage to the muscle and may potentially be associated with edema (32), whereas the prolonged elevation of T2 likely reflects a long-lasting adaptation (12).…”
mentioning
confidence: 95%